Explaining Corruption: A Common Agency Approach - Norbert Maier (Hungarian Academy of Sciences, Institute of Economics, 2004)
In many cases, politicians and government officials are forbidden by law to accept monetary donations from interest groups or other outside parties as these monetary transfers are thought to cause social inefficiencies. The empirical literature supports this view as it finds a negative link between corruption (secret payments to government officials) and growth. However, banning monetary transfers to government officials might be discouraged as it is equivalent to restricting transactions in the market for political decision-making and inefficiencies can arise exactly because of these constraints. In this paper, we address the following question: Under which conditions should the government forbid its officials to accept monetary donations, even though enforcing such bans is costly and secret transfers still may occur? In particular, we analyze a common agency game, in which a government official acts as the common agent of the government and some third party, and identify some conditions under which banning economic interactions between the official and the third party is welfare enhancing. We also explain why secret monetary transfers to government officials can lead to economic inefficiencies.
Keywords: C72; D62; D73; K42; P16; 330; Corruption; Bribing; Common Agency; Exclusive Dealing; Hidden Contracting